All we ever wanted [compact disc, unabridged] : a novel - Giffin, Emily (Random House Audio, 2018)
Nina Browning is living the good life after marrying into Nashville's elite. Her husband's tech business is booming, and her son, Finch, is bound for Princeton. Thomas Talone is a single dad working multiple jobs. His daughter, Lila, was recently accepted to Nashville's most prestigious private high school on a scholarship. Then one devastating photo changes everything. Lila passes out at a party, drunk and half-naked. Finch snaps a picture, types out a caption, and sends it out to a few friends. The photo spreads quickly, and before long, an already divided community takes sides, throws blame, and implodes. And in the midst of it all, Nina and Tom are forced to question all their assumptions about love and loyalty.